2019
DOI: 10.1080/15476286.2019.1637697
|View full text |Cite|
|
Sign up to set email alerts
|

Low level of exosomal long non-coding RNA HOTTIP is a prognostic biomarker in colorectal cancer

Abstract: Molecular risk stratification of colorectal cancer can improve patient outcome. A panel of lncRNAs (H19, HOTTIP, HULC and MALAT1) derived from serum exosomes of patients with non-metastatic CRC and healthy donors was analyzed. Exosomes from healthy donors carried significantly more H19, HULC and HOTTIP transcripts in comparison to CRC patients. Correlation analysis between lncRNAs and clinical data revealed a statistical significance between low levels of exosomal HOTTIP and poor overall survival. This was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 30 publications
0
49
0
Order By: Relevance
“…Mounting evidence has demonstrated that lncRNAs are closely associated with normal physiological progresses and pathological change [26]. The aberrantly expressed lncRNAs could be applied as prediction biomarkers for many diseases, including cancers [27][28][29]. In present study, we found that RHPN1-AS1, as a newly discovered lncRNA, was aberrantly up-regulated in CRC cells than non-tumor one.…”
Section: Discussionmentioning
confidence: 46%
“…Mounting evidence has demonstrated that lncRNAs are closely associated with normal physiological progresses and pathological change [26]. The aberrantly expressed lncRNAs could be applied as prediction biomarkers for many diseases, including cancers [27][28][29]. In present study, we found that RHPN1-AS1, as a newly discovered lncRNA, was aberrantly up-regulated in CRC cells than non-tumor one.…”
Section: Discussionmentioning
confidence: 46%
“…A study focusing on circulating serum exosomes reported that the levels of lncRNA HOTTIP could predict OS of patients with CRC. Also, the expression levels of the same lncRNA could discriminate between CRC and healthy controls (AUC=0.75) 105. Expression levels of serum and tissue hsa_circ_0004585 correlated with CRC tumour size and this circRNA was proposed as a diagnostic biomarker (tissue: AUC=0.731, serum: AUC=0.707) 106.…”
Section: Ncrnas In Cell-to-cell Communication: the New Cancer Biomarkersmentioning
confidence: 99%
“…103 Contrastingly in CRC, exosomal HOTTIP plays different roles. 104 Exosomes from CRC patients demonstrate lower expression level of HOTTIP than those from healthy individuals. As opposed to gastric cancer, patients with low level of exosomal HOTTIP have poor overall survival.…”
Section: E Xosomal Ln Crna S In C An Cer-clini C Al Appli C Ati On Smentioning
confidence: 94%